Multimodal transportation network with cargo containerization technology: Advantages and challenges - Feng, Xuehao; Song, Rui; Yin, Wenwei; Yin, Xiaowei; Zhang, Ruiyou (Transport policy, 2023)
Traditional multimodal transportation dispatching of roads, railways, and maritime has been studied for years. This study investigates a bulk cargo distribution problem in a multimodal transportation network considering both the transportation modes of inland waterways and containerization technology. First, we qualitatively discuss the advantages and challenges of transportation using cargo containerization technology from the aspects of transportation cost, time-saving, pollutant emission reduction, and customer preference. Second, a mixed-integer linear programming model is developed, wherein the influence of bridge heights on transportation is considered. The model is validated based on near-practice numerical experiments, and we can obtain the optimal transportation scenario by solving the model, including transportation mode selection, vehicle routing, depot selection, and cargo quantity for containerization. Third, we conduct numerical experiments based on the multimodal transportation network of the Yangtze River in China to discuss the performance of multimodal transportation with containerization technology considerations. The results show that containerization transportation can decrease the total transportation costs for logistics companies under certain parameter configurations. The model and experiments are then extended by considering pollutant emission reductions and time savings, respectively. We uncover the performance of containerization technology by analyzing the Pareto fronts of this technology and traditional bulk cargo transportation. This study elucidates the decision making of logistics companies and government policymaking.